A thematic review on prophetic leadership in organisations: analysis of patterns and impacts / Siti Syuhada Abd Rahman ... [et al.] - Abd Rahman, Siti Syuhada; Che Senik, Zizah; Wan Hassan, Wan Zulkifli; Yaacob, Salmy Edawati; Zakaria, Zamzuri (Universiti Teknologi MARA, Perlis, 2022)
Prophetic leadership is a model of leadership which is primarily based on the Holy Quran and the exemplary of the Prophets' characteristics. This leadership concept is highly recommended to be practised by Muslim managers in order to achieve blessing from Allah SWT as well as worldly gain. Nevertheless, there has been a relatively small amount of research discussing the patterns in prophetic leadership publications and the positive impacts that it offers. Therefore, the aim of this thematic review paper was twofold, that was to explore the pattern of the publications that discussed prophetic leadership in organisations, and to examine the impact that may be derived from practising prophetic leadership. Three databases including Dimensions, Microsoft Academics, and Google Scholar were searched under the keywords prophetic leadership and Islam. Selected articles were reviewed and analysed using Atlas.ti8 software. The findings from the code-to-document analysis found six research themes on the patterns of publications and derived twelve sub-themes on the impacts of practising prophetic leadership. This study provided an avenue for Muslim managers to improve their leadership style from the Islamic perspective, and also benefits future researchers who would focus on Islamic management and leadership.